Epoxy- and Polyester-Based Composites Reinforced With Glass, Carbon and Aramid Fabrics: Measurement of Heat Capacity and Thermal Conductivity of Composites by Differential Scanning Calorimetry - Cecen, Volkan; Tavman, Ismail H.; Kok, Mediha; Aydogdu, Yildirim (John Wiley & Sons Inc, 2009)
The primary purpose of the study is to investigate the temperature dependence of heat capacity and thermal conductivity of composites having different fiber/matrix combinations by means of heat-flux differential scanning calorimetry (DSC). The materials used as samples in this study were epoxy- and polyester-based composites. Noncrimp stitched glass, carbon, and aramid fabric were used as reinforcements for making unidirectional composites. For the heat capacity measurements the composite sample and a standard material are separately subjected to same linear temperature program. By recording the heat flow rate into the composite sample as a function of temperature, and comparing it with the heat flow rate into a standard material under the same conditions, the temperature dependence of heat capacity of the composite sample is determined. Measurements were carried out over a wide range of temperatures from about 20 to 250 degrees C. The differential scanning calorimeter was adapted to perform the thermal conductivity measurements in the direction perpendicular to the fiber axis over the temperature range of 45-235 degrees C. The method used in this study utilizes the measurement of rate of heat flow into a sensor material during its first-order phase transition to obtain the thermal resistance of a composite material placed between the sensor material and the heater in the DSC. POLYM. COMPOS., 30:1299-1311, 2009. (C) 2008 Society of Plastics Engineers
Keywords: Temperature-Dependence; Dsc; Polymers; Systems; Fibers; Melts